(untitled) (Fiep Bulletin - online, 2011)
The strength training added in schools aims to promote physical condition, prevention and therapy that will contribute to the body development of students (Godoy, 1994). Strenght is a physical quality related to the quality of life and functional independence. In this sense, was performed a descriptive research with 20 professionals of Physical Education of Rio das Ostras and Barra de São João in Rio de Janeiro that work in schools from 1st to 9th grade in order to verify the degree of knowledge of them in relation to the application or not of the strength training in their classes, how they are applied, what are the factors involved and about the ways of procedure known. The results show that teachers in both cities apply strength training in their classes, in Rio das Ostras about 80% of the sample and in Barra de Sao Joao 90% and apply it in a recreational way about 80%. About 50% of the interviewee said they apply it using the body’s own weight or the colleague one. The intervening factor mentioned by Barra de São João, reaching 100% of the sample was the lack of material structure in education, a fact not mentioned by the teachers of Rio das Ostras. As a result, it is noted that teachers from both cities are qualified to apply the topic. Comparing the study of Rio das Ostras and Barra de São João with two other studies that were made in Cabo Frio, it was found a very big difference in relation to the execution of this training, because in both researches that were made in Cabo Frio, teachers said they don’t use this method in their classes, the few who use it, apply it in a wrong way and pointed out also as intervening factor the lack of conditions of the school.